Nivel de comprensión lectora y rendimiento académico en el área de comunicación en estudiantes del cuarto grado de primaria colegio Cooperativo César Vallejo, Iquitos 2022 - Guevara Celis, Tyana Minelly (2023)
The aim of this study was to determine the relationship between the reading comprehension levels and the performance academic in the area of Communication in the in students of the fourth grade of elementary school of the Colegio Cooperativo César Vallejo, 1n Iquitos city, 2022. Materials and methods: It was applied a reading comprehension test for elementary school to 118 childrens, previous validation for experts. The study was descriptive – relational and the design was not experimental. To determine the relationship, it used the non-parametric statistical test Rho of Spearman which applies to ordinal categorical variables. It was observed that the result Rho of Spearman = 0,565 with a significance p = 0 < 0,05. Conclusion: there is a considerable positive and significative correlation between reading comprehension levels and the performance academic in the area of Communication in the students of the fourth grade of elementary school of the Colegio Cooperativo César Vallejo, in Iquitos city, 2022.